Egg-lying behavior of Anisopteromalus calandrae (Howard), an Ectoparasitoid of Lasioderma serricorne (Fabricius) - Oanh, Nguyen Thi; Lan, Tran Ngoc; Lam, Truong Xuan (Academia Journal of Biology, 2017)
This paper describes the egg-laying behavior and reproduction capacity of Anisopteromalus calandrae in laboratory conditions. Anisopteromalus calandrae lay eggs only on the Lasioderma serricorne larvae hiden inside of grains or nests. The maximum lifespan of A. calandrae females was 32 days when they were kept with of aqua feed flour plus honey (30%) and infested with larvae of Lasioderma serricorne. One female laid 71.13 ± 4.24 eggs. The eggs were laid mostly (81.95%) during the first half of the lifespan, with the peak of 7.40 eggs/day on the 9th day. The females usually lay one egg/host larva, but sometimes they lay 2-5 eggs/host larva. They prefer to lay eggs on the 4th larval instar. Citation: Nguyen Thi Oanh, Tran Ngoc Lan, Truong Xuan Lam, 2017. Egg-lying behavior of Anisopteromalus calandrae (Howard), an ectoparasitoid of Lasioderma serricorne (Fabricius). Tap chi Sinh hoc, 39(4): 416-420. DOI: 10.15625/0866-7160/v39n4.10935.* Corresponding author: ntoanh@dthu.edu.vn.Received 17 August 2017, accepted 20 November 2017